Equipping Young Researchers Through Mentorship to Engage in Collaborative Academic Research - Madden, Oneil N; Edwards, Kevol; McKenzie, Nattalie; Smith, Ricardo; Chambers, Rovel (Journal of Education and Practice, 2025)
Purpose: Early-career researchers (ECRs) have various foundational competencies that they need to demonstrate to produce effective research output. Mentors can provide guidance to help them hone their skills and shape their research and professional identity. However, many young researchers do not have structured mentorship or formal avenues to support their research development. This research study sought to explore ECRs perceptions of the skills needed and their research readiness to engage in collaborative research, core attributes of a research mentor, experience working with a research mentor, benefits of collaborative research, and ways to improve research output among ECRs. Methodology: A mixed-methods design was employed. Data were collected from 10 ECRs via an online questionnaire developed in Google Forms and from one interviewee – a research mentor – through a structured interview. Participants were selected through purposive sampling. Data were analysed using qualitative content analysis and descriptive statistics. Findings: Major findings revealed that mentorship plays a valuable role in shaping ECRs research skills and improving confidence, highlighting that research mentors should not only demonstrate academic and technical competence but also psychosocial and soft skills. Additionally, collaborative research brings numerous benefits, including strengthening cross-disciplinary research. Nevertheless, research structures need to be strengthened by deliberate policies, investments, and incentives to boost research output. Unique contribution to theory, practice and policy: The study contributes to the limited literature in Jamaica and the Caribbean concerning mentorship of ECRs. It invites universities and researchers to develop sustainable frameworks to support young researchers, including graduate students and teachers at the lower levels of the education system who are interested in developing and strengthening their research skills. Beyond Jamaica and the Caribbean, the study’s implications are applicable to wider contexts in which ECRs struggle to establish their research identity. Therefore, requisite stakeholders are encouraged to dedicate the necessary funding and mentorship support to improve quality research output.